Threat analysis for more effective lion conservation. Issue 1 (2nd January 2022) - Bauer, Hans; Dickman, Amy; Chapron, Guillaume; Oriol-Cotterill, Alayne; Nicholson, Samantha K.; Sillero-Zubiri, Claudio; Hunter, Luke; Lindsey, Peter; Macdonald, David W.
Abstract: We use comparable 2005 and 2018 population data to assess threats driving the decline of lion Panthera leo populations, and review information on threats structured by problem tree and root cause analysis. We define 11 threats and rank their severity and prevalence. Two threats emerged as affecting both the number of lion populations and numbers within them: livestock depredation leading to retaliatory killing of lions, and bushmeat poaching leading to prey depletion. Our data do not allow determination of whether any specific threat drives declines faster than others. Of 20 local extirpations, most were associated with armed conflicts as a driver of proximate threats. We discuss the prevalence and severity of proximate threats and their drivers, to identify priorities for more effective conservation of lions, other carnivores and their prey.